1984
DOI: 10.1007/bf00432881
|View full text |Cite
|
Sign up to set email alerts
|

The psychiatric significance of dermatitis artefacta

Abstract: A total of 71 patients (12 males and 59 females) who attended the University Skin Clinic of Basle in the years 1956-1982, have been investigated by a dermatologist, a psychiatrist and a psychologist. Among 55 female patients (group I and II) 14 had a suicide attempt in their history. Of the 39 female patients of group I 25 (64%) had suffered from a stressful childhood event. Of group I (39 female patients) 19 (48.7%) had had psychiatric therapy in the past or at the time of investigation; 23 patients (59%) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…The injuries are usually inflicted on the scale of the human hand (fig. 3); owing to the preponderance of right-handers, the self-inflicted injuries are found predominant ly on the left half of the body [29], Prognosis A larger patient collective, consisting of 71 persons with factitious skin lesions, was inves tigated by Hanel et al [26,30]; follow-up examinations in 39 cases confirmed the re sults stated above. Fourteen out of 55 patients included in the study had attempted suicide.…”
Section: Epidemiologymentioning
confidence: 60%
See 2 more Smart Citations
“…The injuries are usually inflicted on the scale of the human hand (fig. 3); owing to the preponderance of right-handers, the self-inflicted injuries are found predominant ly on the left half of the body [29], Prognosis A larger patient collective, consisting of 71 persons with factitious skin lesions, was inves tigated by Hanel et al [26,30]; follow-up examinations in 39 cases confirmed the re sults stated above. Fourteen out of 55 patients included in the study had attempted suicide.…”
Section: Epidemiologymentioning
confidence: 60%
“…Many authors emphasize that factitious disorders can progress, in some cases over years, or exhibit a recidivistic course [26,31,32,46] and call attention to the life-threaten ing nature of the symptomatology [43,47], These statements are based, in many cases, on descriptions of individual cases or on the course of therapy observed in only a few per sons. Very few comprehensive follow-up stud ies have been published.…”
Section: (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 4 out of 6 of their patients, Harnoss et al [4] found early object losses caused by divorce or the death of a parent; this was also true of 44% of the 30 patients studied by Haenel et al [5] who came from a 'broken home' situation. Carney and Brown [6] state that 61 % of their group of 42 patients were 'emotionally de prived in childhood' without describing the exact circumstances; similarly, Sussman and Hyler [7] report that 'the usual history reveals that one or both parents are seen as rejecting figures who are unable to form close relation ships' [p. 1244], Parents of this kind are absent emotionally rather than physically.…”
Section: Object Lossesmentioning
confidence: 92%
“…In general, patients are willing to acknowledge their part in creation of the lesions. Most often, these patients present a personality with perfectionistic and compulsive traits, obsessive-compulsive disorder or depression [Fruensgaard, 1984;Gupta et al, 1987;Haenel et al, 1984;Stein and Hollander, 1992]. Psychosocial stressors have been reported to proceed development of neurotic excoriations in 30-98% of the patients [Fruensgaard, 1984;Gupta et al, 1987;Parsad and Saini, 1997].…”
Section: Neurotic Excoriationsmentioning
confidence: 99%